Enhancing energy storage capacity of iron oxide-based anodes by adjusting Fe (II/III) ratio in spinel crystalline. (9th July 2021) - Jiang, Xiaolin; Chen, Tao; Liu, Bo; Sun, Rongke; Fu, Jiecai; Jiang, Xiao; Cui, Peng; Liu, Zhanqi; Han, Weihua
Abstract: Supercapacitors, as promising energy storage candidates, are limited by their unsatisfactory anodes. Herein, we proposed a strategy to improve the electrochemical performance of iron oxide anodes by spinel-framework constraining. We have optimized the anode performance by adjusting the doping ratio of Fe (II/III) self-redox pairs. Structure and electronic state characterizations reveal that the Ni x Fe3− x O4 was composed of Fe (II/III) and Ni (II/III) pairs in lattice, ensuring a flexible framework for the reversible reaction of Fe (II/III). Typically, when the ratio of Fe (II/III) is 0.91:1 (Fe (II/III)-0.91/1), the Ni x Fe3− x O4 anode shows a remarkable electrochemical performance with a high specific capacitance of 1694 F g −1 at the current density of 2 A g −1 and capacitance retention of 81.58%, even at a large current density of 50 A g −1 . In addition, the obtained material presents an ultra-stable electrochemical performance, and there is no observable degradation after 5000 cycles. Moreover, an assembled asymmetric supercapacitor of Ni–Co–S@CC//Ni x Fe3− x O4 @CC presents a maximum energy density of 136.82 Wh kg −1 at the power density of 850.02 W kg −1 . When the power density was close to 42 500 W kg −1, the energy density was still maintained 63.75 Wh kg −1 . The study indicates that inherent performance of anode material can be improved by tuning the valence charge of active ions.